A COMPARATIVE STUDY OF FIRST EPISODE STATUS EPILEPTICUS AND MULTIPLE EPISODES OF STATUS EPILEPTICUS IN EMERGENCY DEPARTMENT OF TERTIARY HOSPITAL OF BUNDELKHAND REGION, CENTRAL INDIA - Kuldeep; Singh Rajput, Jeetam; Gupta, Virendra; Singh, Ravindra (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Status epilepticus (SE) is a medical emergency that necessitates prompt and intensive treatment to prevent damage to the brain and other complications. SE can occur in any age group, but it is most observed in infants and the elderly. The diagnosis of convulsive SE is primarily clinical, but neuroimaging and laboratory studies are required to identify the underlying cause when convulsion is subsided. Bundelkhand region is a proposed state, located between Uttar Pradesh and Madhya Pradesh in central India, has a population of approximately 18 million, with around 14 million residing in rural areas (Census 2011). This region is infamous for its backward healthcare and education systems. This study aims to compare the outcomes of individuals experiencing their first episode of SE versus those with multiple episodes in terms of seizure control or progression to refractory or super-refractory status, considering the underlying causes. Methods: A total of 100 participants were selected for the study at MLB Medical College, Jhansi, between March 2020 and November 2021. Before participation, written informed consent was obtained after explaining the study’s objectives and procedures in detail. Data were recorded on an Excel sheet and analyzed using the Statistical Package for the Social Sciences software, applying appropriate statistical tests when necessary. Results: Among the 100 patients with SE, the common etiological factors were anticonvulsant drug withdrawal (33%) and central nervous system (CNS) infections (33%), followed by metabolic encephalopathy (17%), cerebral vascular accidents (12%), and hypoxemic encephalopathy (5%). The patients were managed according to standard protocols and drug availability. The outcomes were categorized as seizure control, hospital death, or development of refractory or super-refractory status. Among the patients, 35% developed refractory SE, and within that group, 29% progressed to super-refractory status. Conclusion: The fatality rate of SE was 14.0%. Predictors of higher mortality rates included the first episode of SE, patient’s age, lack of response to initial antiepileptic drugs, duration of convulsions, and untreatable underlying causes. Etiologies such as CNS infections and anticonvulsant drug withdrawal were considered preventable and have better outcomes.